Strategi Public Relations Yayasan Bina Wisata Kelurahan Ubud dalam Mewujudkan Pariwisata Ubud yang Berkelanjutan - Widiarta, Kadek Dharmayeni Putri; Purnawan, Ni Luh Ramaswati; Suryawati, I Gusti Agung Alit (E-Jurnal Medium, 2024)
Ubud area is a world-class tourism destination, which in its sustainability and development requires support from all aspects of stakeholders. This study aims to analyze the public relations strategy that has been implemented by the Bina Wisata Kelurahan Ubud Foundation as a social institution in Ubud Village area which historically played a strategic role in the direction and development of tourism in Ubud. The research method used is descriptive qualitative research. Data collection techniques using interviews and observation. The results showed that, it has implemented a public relations strategy in the foundation's activities and the General Chairperson acts as a communication facilitator in public relations. The public relations strategy is carried out through the foundation's communication program which focuses on public relations activities; 1) Relationship with Other Publics, Community Relations, Government Relations, and Industrial Relations; 2) Investor Relations; and 3) Miscellaneous Activities and needs to expand public relations activities, especially increasing publications and public opinion research.   Keywords: Public Relations Strategy, Public Relations, Bina Wisata Kelurahan Ubud Foundation, Sustainable Tourism.